INTRA-SPECIES GROUPINGS OF CHUM SALMON ONCORHYNCHUS KETA (SALMONIDAE) OF THE AMUR RIVER AND THEIR DISTRIBUTION WITHIN THE BASIN - S. F. Zolotukhin (Известия ТИНРО, 2019)
Chum salmon in the Amur River basin are represented by two races: summer and fall ones. For the summer race, one population with specific type of spawning grounds is known, but the fall race includes three populations with different types of spawning grounds. In total, four eco-geographical groupings of the species are separated in their reproduction by geographical boundaries of geomorphological zones, as well as temporally and ecologically. Chum salmon do not spawn in the Chinese part of the Amur basin in more than 50 years. In the Russian part, the summer chum salmon spawn completely in the hyporheic waters in late July — August, the major grouping of fall chum (77.1 %) spawns in the spring waters in September-November, other two groupings spawn in the hyporheic waters of the lower Amur in September (20.4 %) and in the spring waters of the lakes near the Amur mouth in October-November (2.5 %).